Quality of life among Malaysian patients with vitiligo. - Wong, S.M.; Baba, R. (Blackwell Publishing, 2012)
BACKGROUND: Vitiligo is a chronic disease and can have significant impairment on patients' quality of life (QoL). Studies have shown that limitations in QoL are similar in magnitude to patients with other chronic skin diseases like psoriasis. The objective of this study was to assess the quality of life (QoL) of patients with vitiligo attending the dermatology clinic of a tertiary hospital in Malaysia. METHODS: All patients with a clinical diagnosis of vitiligo who were seen at our dermatology clinic and phototherapy daycare center from September 15 to November 20, 2009 were invited to participate. RESULTS: A total of 102 patients with vitiligo were included in this survey (56.9% females, 43.1% males; mean age 43.6). The mean DLQI score ± SD was 6.40 ± 5.17. The highest mean DLQI score was seen in the patient group aged 30-59 years (mean score 7.05). Malays had significantly higher DLQI scores compared with Indians (P = 0.026). CONCLUSION: Patients in our cohort showed a moderate limitation of QoL, comparable to that of other chronic skin diseases. Management should focus not only on medical treatment but also psychological aspects, hence better QoL and treatment outcomes.